KEBIJAKAN PENDIDIKAN AGAMA ISLAM (PAI) DI INDONESIA DALAM SISTEM PENDIDIKAN NASIONAL - Daulay dan PAsa, Haidar dan Nurgaya Putra dan Pasa (FORUM PAEDAGOGIK, 2014)
AbstractIslamic religious education has been going on since the introduction of Islam to Indonesia. From that time until now there has been dynamics of Islamic education in Indonesia. When Indonesian independence, the one that concerns the government and people of Indonesia is issues related to religious education. To find out about the religious education policy can be traced through the education law in Indonesia starting from the enactment of Law No. 4 of l950 to Act No. 20 of 2003. In the whole of the law, always there is linking it with Islamic education (PAI). It has been so born a number of religious education policies that include Islamic education.Keywords: national education system, the Law of education, Islamic Education